2021
DOI: 10.3389/fendo.2021.696087
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Treatment May Increase Adverse Outcomes in Patients With COVID-19 and Diabetes: A Systematic Review and Meta-Analysis

Abstract: Background and ObjectiveRecently, insulin treatment has been found to be associated with increased mortality and other adverse outcomes in patients with coronavirus disease 2019 (COVID-19) and diabetes, but the results remain unclear and controversial, therefore, we conducted this meta-analysis.MethodsFour databases, namely, PubMed, Web of Science, EMBASE and the Cochrane Library, were used to identify all studies concerning insulin treatment and the adverse effects of COVID-19, including mortality, incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
1
34
0
4
Order By: Relevance
“… 115 Therefore, clinicians should be more vigilant or use additional care while dealing with diabetic patients who are on insulin treatment. 115 , 116 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 115 Therefore, clinicians should be more vigilant or use additional care while dealing with diabetic patients who are on insulin treatment. 115 , 116 …”
Section: Resultsmentioning
confidence: 99%
“…115 Therefore, clinicians should be more vigilant or use additional care while dealing with diabetic patients who are on insulin treatment. 115,116 Several studies have shown that ivermectin has antiviral efficacy against a variety of viruses, in addition to its anti-parasitic properties. It has also been proposed that ivermectin may be beneficial in enhancing the COVID-19 endpoints, owing to its influence on the inhibition of SARS-CoV-2 proteins from accessing the host cell nucleus.…”
Section: Miscellaneous Agentsmentioning
confidence: 99%
“…This may be explained by the fact that insulin use often correlates with disease severity. (40,41) None of the other microdamage outcomes differed by medication use (Table S3). Plate damage did not differ between non-DM and T2DM groups in any orientation; however, longitudinal rods were more damaged in the non-DM group than the T2DM group (non-DM DV longitudinal rods /BV longitudinal rods + 72% versus T2DM, p = 0.027) (Fig.…”
Section: Plate Microdamage Normalized By Plate Volume and Rod Microda...mentioning
confidence: 99%
“…The major contributing factors for more severe clinical forms of COVID-19 in obesity are associated respiratory dysfunction [132,133], overexpression of ACE2 in adipocytes, chronic systemic inflammation, and immune system hyperactivation [62,134,135]. Subjects with a BMI over 30 kg/ m 2 have a greater risk of death by COVID-19 [72,75,136], even after controlling for age and sex [71,137].…”
Section: Obesitymentioning
confidence: 99%